STUDI PENELURUSAN KINERJA PENGELOLAAN SARANAPRASARANA DAN SISTEM MANAJEMEN LABORATORIUM IPA PADA TINGKAT MADRASAH TSANAWIYAH (MTs) SEKABUPATEN JENEPONTO - Said L., Muh (Teknosains: Media Informasi Sains dan Teknologi, 2014)
This research about study sighting of fasility and laboratory management of Natural Sciences. at level of Madrasah Tsanawiyah (MTS) Se-Kabupaten Jeneponto. This formula research internal issue is (1) What is the equipment of laboratory facilities and basic facilities of Natural Sciences. by school of madrasah se-Kabupaten Jeneponto fulfill minimum standard which specified by Institute Standard National Education?; ( 2) How is laboratory management of Natural Sciences by existing MTS se-Kabupaten Jeneponto?; This research have been conducted with a few method intake of data that is observation, admission filling of enquette, direct interview and documentation photograph result of survey. Data analysis in this research is used analytic descriptive method that is intake of quantitative data, then analysed descriptive statistically. Result of research obtained that (1) laboratory facilities and basic facilities of natural sciences by the school of madrasah MTS se- Kabupaten Jeneponto not yet fulfilled minimum standard which specified by Institute Standard National Education and not yet is maximal of management performance meanly; ( 2) Laboratory management system of natural sciences by existing MTs obtained meanly assess the understanding of interest standard lead laboratory that is 3,14 namely good category, but application in streamlining activity of management of laboratory not yet maximal and not yet according of attainment goals.